Dysregulated monocyte-derived macrophage response to Group B Streptococcus in newborns - Ravi, Denho; Ntinopoulou, Erato; Guetta, Nessim; Weier, Manuela; Vogel, Verena; Spellerberg, Barbara; Sendi, Parham; Gremlich, Sandrine; Roger, Thierry; Giannoni, Eric (Frontiers in Immunology, 2023)
Streptococcus agalactiae (Group B Streptococcus, GBS) is a leading pathogen of neonatal sepsis. The host-pathogen interactions underlying the progression to life-threatening infection in newborns are incompletely understood. Macrophages are first line in host defenses against GBS, contributing to the initiation, amplification, and termination of immune responses. The goal of this study was to compare the response of newborn and adult monocyte-derived macrophages (MDMs) to GBS. Monocytes from umbilical cord blood of healthy term newborns and from peripheral blood of healthy adult subjects were cultured with M-CSF to induce MDMs. M-CSF-MDMs, GM-CSF- and IFNγ-activated MDMs were exposed to GBS COH1, a reference strain for neonatal sepsis. GBS induced a greater release of IL-1β, IL-6, IL-10, IL-12p70 and IL-23 in newborn compared to adult MDMs, while IL-18, IL-21, IL-22, TNF and RANTES/CCL5, MCP-1/CCL2 and IL-8/CXCL8 were released at similar levels. MDM responses to GBS were strongly influenced by conditions of activation and were distinct from those to synthetic bacterial lipopeptides and lipopolysaccharides. Under similar conditions of opsonization, newborn MDMs phagocytosed and killed GBS as efficiently as adult MDMs. Altogether, the production of excessive levels of Th1- (IL-12p70), Th17-related (IL-1β, IL-6, IL-23) and anti-inflammatory (IL-10) cytokines is consistent with a dysregulated response to GBS in newborns. The high responsiveness of newborn MDMs may play a role in the progression of GBS infection in newborns, possibly contributing to the development of life-threatening organ dysfunction.